ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RISK-BASED BANK RATING (RBBR) (STUDI PADA BANK YANG TERDAFTAR DI BANK INDONESIA DALAM LAPORAN TRIWULANAN PERBANKAN TAHUN 2015) - Rezaldi, Bayu; Sutanto, Aftoni (Universitas Ahmad Dahlan, 2017)
The research objective is to understand bank’s health rate that are listed in Bank Indonesia in banking sub-sector period 2015. Bank’s health rate is assessed through Risk-Based Bank Rating method which includes four factors such as risk profile, Good Corporate Governance,, earning and capital of each bank. This research only considers three factors of four total factors Risk Profile is proxied by Loan to Deposit Ratio(LDR), Earning is proxied by Return On Asset (ROA) to Net Interest Margin (NIM), Capital is proxied by Capital Adequacy Ratio (CAR). The assessment of bank’s health rate based on Risk Profile with Loan to Deposit Ratio analysis has shown that some bank area not heahlty with Loan to Deposit Ratio below 85% , the assessment based on earning with Return On Asset analysis has shown that some banks are not healthy with Return On Asset below 1.25 %. The assessment with Net Interest Margin has shown that some bank are not healthy with Net Interest Margin below 2%. The assessment based on capital by Capital Adequacy Ratio shows positive result for each bank. In general, each bank has Capital Adequacy Ratio aboved 10 %. Considering these results, each bank in healthy category.